EFFECT OF MAGNETIC FIELD ON THE GROWTH, MULTIPLICATION AND CONCENTRATION OF THE VOLATILE OIL OF ROSEMARY OFFICINALIS IN VITRO - & Jawad, Abdul Husain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was conducted at the plant tissue culture laboratory – Dept. of Horti.- Coll. of Agricultural Engineering Sciences – Univ. of Baghdad, in order to study the effect of magnetic field in the propagation and production of volatile oil compounds of rosemary plant Rosmarinus officinlis. Factorial experiments within completely randomized design with thirty replications were used. The results indicated  an increase in the treatment of exposure to south pole for 30 days with the highest mean of the shoots number, fresh and dry weight and total chlorophyll content (7.5 shoots.plant-1, 6634 mg, 769.5 mg and 160.6 mg.100 g-1) respectively. While the control treatment produced the lowest value of shoot number, fresh and dry weight and total chlorophyll content (5.7 shoots.plant-1, As shoots length, the exposure to south pole for 30 days, gave the shoot length (6 cm), while the exposure treatment to north pole for 20 days gave mean branch length of 2.25 cm. In terms of the effect of magnetic field on the concentration of volatile oil compounds, the results indicate that the exposure to south pole for 30 days significantly higher than the other treatments in the following compounds: linalool, Terpinene, linderol, Limonene cymene, and camphor penene. The 30-day north pole exposure was significantly higher in the two compounds: merycenen and sabinene.